The use of Core Competencies in Suicide Risk Assessment and Management in supervision: a feminist-narrative approach - Drake, Adryanna Siqueira (My University, 2013)
Therapists-in-training receive limited training in how to perform suicide risk assessment and management. This task is generally left for clinical supervision. In fact, one-to-one supervision is the most critical element in helping supervisees become skilled at assessment and management of suicide risk. This article proposes the use of the Core Competencies for Suicide Risk Assessment and Management (Suicide Prevention Resource Center, 2006), using feminist and narrative family therapy perspectives. This approach is meant to foster competence and confidence necessary for supervisees to perform suicide risk assessment and management. Specific tools for supervision are provided.
Keywords: Suicide; Supervision; Narrative therapy; Feminist therapy; Assessment; Confidence